Disentangling the ISM phases of the dwarf galaxy NGC 4214 using [C II] SOFIA/GREAT observations - Fahrion, Katja; Cormier, Diane; Bigiel, Frank; Hony, Sacha (Arxiv, 2016)
The [CII] 158 um fine structure line is one of the dominant cooling lines in the interstellar medium (ISM) and is an important tracer of star formation. Recent velocity-resolved studies with Herschel/HIFI and SOFIA/GREAT showed that the [CII] line can constrain the properties of the ISM phases in star-forming regions. The [CII] line as a tracer of star formation is particularly important in low-metallicity environments where CO emission is weak because of the presence of large amounts of CO-dark gas. The nearby irregular dwarf galaxy NGC 4214 offers an excellent opportunity to study an actively star-forming ISM at low metallicity. We analyzed the spectrally resolved [CII] line profiles in three distinct regions at different evolutionary stages of NGC 4214 with respect to ancillary HI and CO data in order to study the origin of the [CII] line. We used SOFIA/GREAT [CII] 158 um observations, HI data from THINGS, and CO(2-1) data from HERACLES to decompose the spectrally resolved [CII] line profiles into components associated with neutral atomic and molecular gas. We use this decomposition to infer gas masses traced by [CII] under different ISM conditions. Averaged over all regions, we associate about 46% of the [CII] emission with the HI emission. However, we can assign only around 9% of the total [CII] emission to the cold neutral medium (CNM). We found that about 79% of the total molecular hydrogen mass is not traced by CO emission. On average, the fraction of CO-dark gas dominates the molecular gas mass budget. The fraction seems to depend on the evolutionary stage of the regions: it is highest in the region covering a super star cluster in NGC 4214, while it is lower in a more compact, more metal-rich region.
Gesehen am 25.10.2017